Comment on "Magnetic-field-enabled resolution enhancement in super-resolution imaging" by M. Zhang et al., Phys. Chem. Chem. Phys., 2015, 17, 6722–6727. Issue 6 (24th January 2017) - Bergmann, Stephan; Mönkemöller, Viola; Huser, Thomas
Abstract : Spectral fluorimetry demonstrates that common organic fluorophores such as Alexa 647 exhibit no magnetic field enhanced fluorescence in the absence/presence of a strong magnet. Abstract : Certain fluorophores, in particular those that can undergo photoinduced radical pair reactions are known to exhibit a magnetic field dependent fluorescence summarized in the term magnetic field effect (MFE). We tried to reproduce experiments that reported magnetic field enhanced fluorescence for commonly used organic dyes with a high quantum yield suitable for single molecule localization microscopy. We find that the enhanced fluorescence is due to fluorescence reflected by the magnet's surface rather than MFE.